ADSORPTION OF Cr(VI) USING NATURAL ZEOLITE IMPREGNATED WITH FeO AND CARBON - Rizkia Widyawati, Yudith
The development of the industrial sector in the world, especially in Indonesia, is increasingly developing by the time. The industrial sector in West Java is dominated by manufacturing industries such as textiles, paper, pharmaceuticals, food and beverage products and electroplating. To improve the quality of effluent, especially in the parameters of heavy metals, it is necessary to treat before the effluent discharged into the water body. In this study batch and continue adsorption of Cr(VI) experiments have been carried out using widely available materials in nature, Zeolite, it was modified with the impregnation method using iron oxide and carbon. Natural zeolite is modified to increase its adsorption ability. Based on the results of XRD characterization, it is known that the impregnation of FeO on zeolite has been successfully carried out which is indicated by the emergence of a specific peak of iron oxide and it is known that FeO particles size formed are 48,12 nm. The SEM-EDX results show that there are around 2,15% FeO and 1,44% carbon formed on the zeolite surface. In the adsorption stage, the variation of the type of adsorbent, contact time, pH, initial concentration of Cr(VI) and the adsorbent dose were observed. Based on the results of batch experiments the optimum conditions tend to be at acidic pH i.e pH 2, the initial concentration of Cr(VI) 2 mg/L using 20 grams of Zeolite-FeO/C for 60 minutes treatment time at room temperature with a rotation speed of 140 rpm. In optimum conditions, the efficiency of adsorption Cr(VI) was 80,06%, within a decrease in concentration from 2 mg/L to 0,4044 mg/L. The adsorption capacity obtained at optimum conditions is 0,0199 mg/g. Based on the isotherm model, adsorption of metal ions Cr(VI) using Zeolite-FeO/C follows the Freundlich isotherm model, and pseudo-first-order kinetics. In continyus system it was obtained removal efficiency reach 100% in early treatment until 25hour breakthrough point. The value of rate constant is 0,3113 mL/min/mg with sorption capacity about 0,0874 mg/g and 2,59 L of wastewater volume that can be treated.